Vegetation cover dynamics along two Himalayan rivers: drivers and implications of change - Beale, John; Grabowski, Robert C.; Lokidor, Pauline Long'or; Vercruysse, Kim; Simms, Daniel M. (Elsevier, 2022)
Rivers are dynamic landscape features that change in response to natural and anthropogenic factors through hydrological, geomorphic and ecological processes. The severity and magnitude of human impacts on river system and riparian vegetation has dramatically increased over the last century with the proliferation of valley-spanning dams, intensification of agriculture, urbanization, and more widespread channel engineering. This study aims to determine how changes in geomorphic form and dynamics caused by these human alterations relate to changes in channels and riparian vegetation in the lower Beas and Sutlej Rivers. These rivers are tributaries of the Indus that drain the Western Himalayas but differ in the type and magnitude of geomorphic change in recent decades. Winter season vegetation was analysed over 30 years, revealing increasing trends in vegetated land cover in the valleys of both rivers, consistent with large-scale drivers of change. Greater trends within the active channels indicate upstream drivers are influencing river flow and geomorphology, vegetation growth and human exploitation. The spatial patterns of vegetation change differ between the rivers, emphasizing how upstream human activities (dams and abstraction) control geomorphic and vegetation community response within the landscape context of the river. The increasing area of vegetated land is reinforcing the local evolutionary trajectory of the river planform from wide-braided wandering to single thread meandering. Narrowing of the active channels is altering the balance of resource provision and risk exposure to people. New areas being exploited for agriculture are exposed to greater risk from river erosion, inundation, and sediment deposition. Moreover, the change from braided to meandering planform has concentrated erosion on riverbanks, placing communities and infrastructure at risk. By quantifying and evaluating the spatial variations in vegetation cover around these rivers, we can better understand the interaction of vegetation and geomorphology alongside the impacts of human activity and climate change in these, and many similar, large systems, which can inform sustainable development.
Keywords: Fluvial geomorphology; Vegetation; Remote sensing; NDVI; Land cover; Landsat